Ansätze zur Integration von Flächennutzungsund Verkehrsplanung. Analyse der politischen Dimension integrierter Planung - Levin-Keitel, Meike; Reeker, Irina Kim (Raumforschung und Raumordnung | Spatial Research and Planning, 2021)
Spatial structures influence our travel distances between home, work, shopping or leisure and determine our mobility behaviour to a considerable extent. Although they are not the only determinants of our daily travel distances and times or our choice of different means of transport, the interrelations between spatial structures and mobility behaviour is often considered in the literature. Overall, the integration of land use and transportation planning is a key aspect in the shift towards sustainablemobility. This integrated planning approach is characterised, for instance, by increased cross-sector interaction, softened institutionalised boundaries between the two sectors of land-use and transportation planning, and shared cross-sector goals. In its implementation, however, this frequently postulated call for integration remains unclear. This paper uses the conceptual framework of the three dimensions of policy, polity and politics to empirically capture this integration in its various aspects. The two German cities of Dortmund and Hannover serve as case studies. The findings suggest that informal interaction (politics) between the two sectors is a necessary precondition for integration, while political will and cross-sectorally shared strategic goals (policy) are required to actually set the process of integration in motion. Ultimately, an approach is fully integrated when institutional structures (polity) are adapted in the sense of hierarchical coordination and the extensive elimination of sectoral boundaries.
Keywords: integrated planning; transport planning; cenceptualisation of integration; policy; politics; polity; Dortmund; Hannover